Characterization and exploitation of piston ring chips in the rectification process a new recycling proposal - Teixeira,A. (2010)
The rough grind machine operation in metallic material produce a sub product with the followings components such as: metallic residue, small parts come from the resin grinds, diatomaceous earth material (filter material) and soluble oil in water for tools cooling. According [HU1UH] from ABNT, this sub product is toxic, not inert material, aggress the environment with pollution in the currency water and contaminate the ground when incorrectly go to the municipal solid waste. The final destination of this sub product, is the incineration, in the cements company, being the incorporated the sub product to the cement, during your production. With the qualitative result using the scanning electron microscopy (SEM), coupled to the dispersive energy spectroscopy (EDS), two experiments were made with objective to separate the magnetic material of the non-magnetic material, using a permanent magnet. We conclude that the magnetic material can be used by powder metallurgy process in production of pieces.